The pathogenic role of succinate-SUCNR1: a critical function that induces renal fibrosis via M2 macrophage - Min Pu; Jing Zhang; Fuyan Hong; Yan Wang; Chengwei Zhang; Yongcheng Zeng; Zhenzhen Fang; Weiwei Qi; Xia Yang; Guoquan Gao; Ti Zhou (Cell Communication and Signaling, 2024)
Abstract Background Renal fibrosis significantly contributes to the progressive loss of kidney function in chronic kidney disease (CKD), with alternatively activated M2 macrophages playing a crucial role in this progression. The serum succinate level is consistently elevated in individuals with diabetes and obesity, both of which are critical factors contributing to CKD. However, it remains unclear whether elevated succinate levels can mediate M2 polarization of macrophages and contribute to renal interstitial fibrosis. Methods Male C57/BL6 mice were administered water supplemented with 4% succinate for 12 weeks to assess its impact on renal interstitial fibrosis. Additionally, the significance of macrophages was confirmed in vivo by using clodronate liposomes to deplete them. Furthermore, we employed RAW 264.7 and NRK-49F cells to investigate the underlying molecular mechanisms. Results Succinate caused renal interstitial macrophage infiltration, activation of profibrotic M2 phenotype, upregulation of profibrotic factors, and interstitial fibrosis. Treatment of clodronate liposomes markedly depleted macrophages and prevented the succinate-induced increase in profibrotic factors and fibrosis. Mechanically, succinate promoted CTGF transcription via triggering SUCNR1-p-Akt/p-GSK3β/β-catenin signaling, which was inhibited by SUCNR1 siRNA. The knockdown of succinate receptor (SUCNR1) or pretreatment of anti-CTGF(connective tissue growth factor) antibody suppressed the stimulating effects of succinate on RAW 264.7 and NRK-49F cells. Conclusions The causative effects of succinate on renal interstitial fibrosis were mediated by the activation of profibrotic M2 macrophages. Succinate-SUCNR1 played a role in activating p-Akt/p-GSK3β/β-catenin, CTGF expression, and facilitating crosstalk between macrophages and fibroblasts. Our findings suggest a promising strategy to prevent the progression of metabolic CKD by promoting the excretion of succinate in urine and/or using selective antagonists for SUCNR1.